High‐frequency radio properties of central AGNs in cluster environments. Issue 1 (February 2016) - Baek, J.; Chung, A.; Tremou, E.; Sohn, B. W.; Jung, T.; Ro, H.
Abstract: We present K‐band (22 GHz) properties of 10 central AGNs in galaxy clusters of various dynamic states. The data were obtained using the Korean VLBI Network (KVN) with a goal to study how the AGN hosted by the central cluster galaxy interacts with the cluster core while undergoing feedback. In KVN single‐dish observations, 9 out of 10 targets are detected. Using our K‐band flux and archival low‐frequency radio data, we evaluate spectral indices of the sample. We find a rough trend that central AGNs in the cluster with shorter cooling timescale show a more flat radio spectrum. This result is suggestive of young synchrotron age of the AGNs located in the cluster with a cool core. High resolution KVN VLBI follow up observations indicate some hints of the presence of parsec‐scale jets only in the cool core cluster AGNs. To‐gether with our finding from KVN single‐dish observations, the parsec‐scale jet morphology of the sample suggests that the AGNs in cool‐core clusters are more recently (re)activated compared to their counterparts in non cool‐core clusters. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)